Anesthetic management of folders with severe kyphosis in ankylosing spondylitis: a single-center retrospective case series study - Peng, Lin; Li, Qiang; Zheng, Lingxi; Zhao, Deng; Fu, Qiang (Frontiers in Medicine, 2025)
BackgroundAnkylosing spondylitis (AS) is a progressive inflammatory disease causing severe kyphosis, which complicates surgical management and increases complication risks. This study aims to analyze the characteristics of severe kyphosis in AS and explore methods to optimize perioperative management and reduce complications.MethodsWe conducted a retrospective analysis of clinical data from five patients with severe kyphosis in AS who underwent surgery between October 2017 and February 2022. The patients had a mean age of 40.20 ± 8.50 years. The analysis included pathophysiological changes in folded patients and perioperative multidisciplinary intervention guidance. It also covered strict preoperative anesthetic evaluations, establishing an optimal fluid pathway during surgery, precise anesthetic monitoring and management, and applying postoperative multimodal analgesia and rehabilitation exercises to optimize perioperative anesthetic management.ResultsPreoperative cardiopulmonary function exercises were required to ensure patients could withstand surgery and anesthesia. Awake fiberoptic tracheal intubation was used to ensure airway safety and anesthesia. Hemodynamic evaluation and management were conducted using PICCO monitoring. Somatosensory evoked potentials (SSEP) and myogenic motor evoked potentials (MMEP) were utilized for neural axis monitoring. Hypothermia was designed to protect the spinal cord. To prevent massive blood loss, controlled hypotension and autotransfusion were implemented.ConclusionThe correction operation of severe spinal kyphosis is complex and requires a detailed anesthesia plan. Optimizing the management of difficult airways and respiratory regulation, guiding circulation and fluid management through comprehensive monitoring, avoiding factors that aggravate complications, improving postoperative analgesia, and encouraging active rehabilitation exercises are crucial goals for perioperative anesthesia management.